Physical health impairment, disability and suicidal intent among self-harm survivors in South India - Majgi, Sumanth Mallikarjuna; Jones, Steven; Taylor, Lou; R., Somashekar; Nagaraj, Santhosh; U., Bharath D.; Krishna, Murali (International Journal Of Community Medicine And Public Health, 2021)
Background: Suicide is major public health concern in India. There are limited data examining the relationship between health impairment, disability and severity of suicidal intent. The aim of the study was to examine the associations of health impairment and disability with severity of suicidal intent among survivors following an act of self-harm. Methods: A pilot exploratory study of 453 self-harm survivors from a specialist hospital in South India. Socio-demographics, physical health impairment, disability (WHO Disability Schedule-II), suicidal intent, (Pierce suicide intent scale) and mental disorders were studied. Results: Arthritis was the most common physical impairment among self-harm survivors followed by gastrointestinal, sensory impairment and difficulty with mobilization. Nearly 10% of participants had some degree of functional impairment, with 38% experiencing severe physical pain in the week prior to self-harm. Past history of depression treatment, age, education and occupation influenced positively PSIS scores. There were significant associations between suicidal intent and disability. Conclusions: Indian self-harm survivors indicated complex relationships between physical health, disability and suicidal intent. Understanding these associations may help to develop suicide prevention strategies. Our findings suggest a need for integrating a comprehensive of physical health assessment in self harm survivors.